2018
DOI: 10.2478/logos-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Application of the WetSpass simulation model for determining conditions governing the recharge of shallow groundwater in the Poznań Upland, Poland

Abstract: Assessments of the infiltration recharge of groundwater are performed using various methods and on different scales. Infiltration is dependent of climatic factors, aspects of water circulation, as well as on quasi-stationary and variable environmental features of a specific area, which are frequently difficult to determine on the basis of direct measurements or observations. The objective of the present study was to identify factors conditioning recharge of shallow groundwater in selected catchment areas of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Effective infiltration of precipitation, that is, groundwater net recharge, means the part of the rainfall that percolates to the saturation zone, as indicated by [34], among others. An overview of recharge evaluation methods is given, for example by [34,35]. One of many methods giving a spatially variable result is the Wet Spass water balance model [36].…”
Section: Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective infiltration of precipitation, that is, groundwater net recharge, means the part of the rainfall that percolates to the saturation zone, as indicated by [34], among others. An overview of recharge evaluation methods is given, for example by [34,35]. One of many methods giving a spatially variable result is the Wet Spass water balance model [36].…”
Section: Lowmentioning
confidence: 99%
“…One of many methods giving a spatially variable result is the Wet Spass water balance model [36]. Factors conditioning the recharge of shallow groundwater in selected catchments using the Wet Spass model with a spatially distributed parameter were identified by [35], among others. Their study revealed, inter alia, that changes in relationships between components of water balance having similar distributions are caused by differences in the type of land usage.…”
Section: Lowmentioning
confidence: 99%
“…The publications by Aish et al (2010), Mogheir and Ajjur (2013) and Gharbia et al (2015a, b) discussed the influence of climate change on the groundwater resources in the Gaza Strip. The objective of the study Graf and Przybyłek (2018) was to identify factors conditioning recharge of shallow groundwater in selected catchment areas of the Poznań Upland using the WetSpass simulation water balance model with spatially distributed parameters. Another research aimed to use WetSpass model to estimate long-term average annual and seasonal groundwater recharge for Birki watershed (45 km 2 ) in northern Ethiopia using long-term (10 years) hydro-meteorological and biophysical (soil, land use, topography, slope and groundwater depth) data of the watershed (Meresa and Taye 2018).…”
Section: Introductionmentioning
confidence: 99%